High seed viability recorded in an endangered endemic species, 'Isoplexis isabelliana' (Scrophulariaceae), after more than 30 years of storage in a conservation seed bank - González Pérez, Miguel Ángel; Cabrera-García, Nereida; Cayon-Fernández, Isabel (Mediterranean Botany, 2021)
Conservation seed banks are essential for ex-situ conservation of genetic biodiversity. These institutions are especially relevant for threatened species and play a vital role in their conservation by preserving genetic material. However, samples deposited in the seed banks must germinate when necessary to use them (i.e., recovery plans, etc.). This study uses four accessions of the endemic endangered species from Gran Canaria Island (Canary Islands), Isoplexis isabelliana (Webb & Berthel.) Masf. (Scrophulariaceae). Germination tests were carried out to measure seed viability through time and the possible impact of seed storage on their viability. These accessions have been kept in the seed bank for four months to thirty years under different storage conditions. Germination results differed for seeds after 45 days of exposition using 16 hours light and 8 hours darkness at 17 °C. Accessions kept in the seed bank, independently of storage, showed a high germination percentage (89%). Whereas the accessions with rough storage conditions showed a 0% germination rate. The results highlighted the good state of conservation of the material deposited in the Seed Bank of the Botanical Garden "Viera y Clavijo" and the reliability of the temperature and humidity conditions in which the seeds of I. isabelliana have been stored. We consider these results as momentous since several natural populations of I. isabelliana has been affected by the last forest fire on the island.